The therapeutic and integrative significance of faith in the African quest for healing and wholeness - Chiroma, Nathan H. (HTS teologiese studies, 2020)
The therapeutic and integrative significance of faith in the African quest for healing and wholeness has attracted a considerable level of interest amongst scholars in recent times. Despite the increasing interest in places of healing, faith communities have not paid much attention to studying the intersection of these practices for appropriate community hermeneutics. By means of qualitative methods, this research explored the therapeutic implication of the role of faith in the quest and appropriation of health and wholeness in modern Africa. Exploring perspectives from Ghana and Nigeria, the study engaged, through focus groups and individual interviews, the proper place of therapeutic significance of faith in the quest for healing and wholeness. Findings revealed that the African quest for health and wellness is anchored in the belief of a deity whose presence, love and benevolence transcend the ecclesiastical boundaries of one’s faith tradition. The study further describes the therapeutic and integrative significance of these prevailing faiths in God within the appropriation of health and wholeness in modern Africa, with the possibility of fostering a partnership amongst the three key players in the triangulation process.Contribution: The study falls within the field of practical theology and its major contribution falls within the quest of wellness and healing in Africa.